Approche comparative de la qualité des sols entre le semis direct et le labour conventionnel - Kari Ayat Ellah, Mohamed Elhabib; Benkhelifa, Mohamed (My University, 2022)
The comparative study of the work, the quality of the grounds between the direct seeding and the conventional plowing in Algerian arid zone showed a difference in behavior of the cultures and an evolution of the characteristics of the ground. First of all, the conventional mode expresses the highest yield compared to simplified techniques and direct seeding. After the practice of no plowing gave the best yields, an increase of 10 q-ha (durum wheat) compared to conventional practices. This confirms that the production of wheat in direct seeding is better with the increase in the duration of its practice. However, the high soil humidity conditions at the time of sowing resulted in poor emergence and therefore a lower yield. The soil characteristics also revealed differences on the three tillage modes. Indeed, a better water retention capacity of the soil is measured on no-tillage, as well as better marked organic matter content on each of the different plots studied. Comparison of bulk density shows clear variation and the largest value marked on conventional work